An integrative approach to intercultural communication in context : empirical evidences from higher education - Ayalew, Anteneh Tsegaye; Justus Liebig University Giessen (My University, 2012)
Applying an exploratory mixed-methods research, ethnographic and quantitative findings were generated to describe and explain intercultural communication perceptions and experiences in a higher educational context in Ethiopia. The qualitative findings revealed that diversity has been prevalent among students but not in the staff or administration. The campus has been characterized as a divided academic community, exercising high power distance and lacking an effective communication system. Ethnicity appeared to be the most stratifying factor on campus interaction. The major challenges of intercultural communication were ethnicity, political affiliation, high power distance, disparity in host language proficiency, lack of a supportive context and deficiency in intercultural skills and awareness. Multiculturalism as an educational policy has not helped the university address the grievance consequences of the divided educational context. Based on the results, interculturalism, incorporating intercultural communication as its integral part, was recommended as a working educational policy.It was reported that intercultural competency was significantly correlated with intercultural relations (r = .369, p < .01), communicating in the host languages (English, (r = .302, p < .01) and Amharic (r = .219, p < .01)), and intercultural collaboration (r = .299, p < .01). It was also positively correlated with intra-cultural relations (r = .199, p < .01) and intra-cultural collaboration (r = .234, p < .01). In line with the theory of intercultural competence, respondents with higher intercultural competency can successfully build intercultural relations (beta = .357), t (284) = 41.383, p = .000); respondents who perceived greater use of the host languages in their communication had a stronger intent to form intercultural relationships (Amharic: (beta = .106), t(282) = 16.686, p = .039); English: (beta = .107), t(282) = 16.686, p = .039). Intercultural collaboration was also found to be a significant predictor of intercultural relations (beta = .237), t (281) = 17.199, p = .000). The youth reported a higher degree of cultural identity salience (CIS) rather than ethnic identity salience (EIS) (t [279] = -14.403, p= .000). Boys rated their ethnic identity salience higher than their female counterparts (t [278] = 4.471, p= .000). There was statistically a significant difference in EIS among ethnic students (F [5,256] =6.768, p= 0.00). The most dominant conflict styles preferred by respondents were integrating, compromising, dominating and avoiding in the order [F (4, 273) = 94.43, p = .0001]. The effect of EIS on dominating conflict style was significant (F [19,273] =2.128, p=0.006) while CIS was significant on integrating conflict styles (F [18,273] =3.380, p= 0.000).
Ein integrativer Ansatz zur interkulturellen Kommunikation im Kontext de Hochschule : Eine empirische Studie
Keywords: Intercultural communication; culture; communication; intercultural competence; higher education; conflict styles; interculturalism; ddc:420